Paediatric non-heart-beating renal transplantation. Issue 10 (6th July 2010) - Edwards, Anusha G; McCarthy, Hugh; Morgan, Justin D; Saleem, Moin A
Abstract : Expanding donor numbers for paediatric transplantation is an urgent, difficult issue. The use of non-heart-beating donor renal transplants has seen a revival in adult practice, with encouraging results. The authors present the first two cases in the UK of paediatric renal transplant from non-heart-beating donors.